Experimental Assessment of a Decentralized Control Strategy for a Back-To-Back Modular Multilevel Converter Operating in Low-Frequency Ac Transmission - Diaz-Diaz, M; Ibaceta-Valenzuela, E; Rajendran, S (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The Modular Multilevel Converter (MMC) has been widely used in high-power applications owing to its inherent advantages, including scalability, modularity, high-power density, and fault tolerance. MMCs have recently been used in Low-Frequency Alternating Current (LFAC) transmission, particularly in the integration of offshore wind power with onshore grids. However, LFAC applications produce significant voltage oscillations in floating capacitor voltages within the MMC. Early research efforts have successfully established and validated decoupled control strategies for LFAC-based MMC systems. However, validations are usually based on simulations or small-scale prototypes equipped with limited power cells. Consequently, this paper presents a decentralized voltage control strategy based on Nearest Level Control for an MMC-based LFAC system. Experimental results obtained with a 120-cell MMC prototype are presented to validate the effectiveness and operation of the MMC in LFAC applications. © 2024 by the authors.